Damage detection of steel moment frames under earthquake excitation. Issue 10 (24th July 2020) - Ebrahimi, Mehrdad; Karami Mohammadi, Reza
Summary: This paper investigates the effects of uncertainties and modeling errors on the performance of nonlinear updating process through an experimental study on two 1/8‐scale four‐story steel moment‐resisting frames. To examine the accuracyo of the models calibrated using different data features and modeling assumptions, the actual structural responses obtained from shaking table tests and the response of the models have been compared. The modeling uncertainties are investigated by applying frames with different modeling assumptions, including concentrated and distributed plasticity, and different hysteretic material behaviors. To calibrate the models, four data features are considered and combined: (1) acceleration time history, (2) displacement time history, (3) instantaneous characteristics of the decomposed monocomponent of the response, and (4) dissipated energy. In this paper, a sensitivity analysis has been performed to investigate the effect of various parameters of hysteretic materials on the response of reference steel moment‐resisting frames. To this end, the optimum values of the unknown parameters are determined through minimizing the objective function defined based on the residuals of data features for the actual structure and finite element (FE) model. By comparing the structural responses of the model with concentrated plasticity calibrated by instantaneous characteristics with those of the other models, it can be concluded that the concentrated plasticity model predicts a more accurate response compared to the other models. Consequently, the aleatory uncertainty was taken into account by evaluating the performance of the system with concentrated plasticity under 40 seismic ground motions, and the structural response has been obtained through the calibrated model.